2021
DOI: 10.1007/s12571-021-01179-3
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity related to agricultural practices and household characteristics in rural communities of northeast Madagascar

Abstract: Ending hunger and alleviating poverty are key goals for a sustainable future. Food security is a constant challenge for agrarian communities in low-income countries, especially in Madagascar. We investigated agricultural practices, household characteristics, and food security in northeast Madagascar. We tested whether agricultural practices, demographics, and socioeconomics in rural populations were related to food security. Over 70% of respondents reported times during the last three years during which food f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 58 publications
(92 reference statements)
4
17
0
Order By: Relevance
“…Households engaged in agricultural activity in the form of crop, livestock, or both crop and livestock production are less likely to experience severe HFI. This finding is similar to several studies that have shown that engaging in agricultural activity can improve food security status in developing countries [ 29 , 69 , 70 , 71 , 72 ]. A study by Pawlak and Kolodziejczak (2020) found that increasing agricultural activities is a key driver of improving food availability and access in rural areas of developing countries [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Households engaged in agricultural activity in the form of crop, livestock, or both crop and livestock production are less likely to experience severe HFI. This finding is similar to several studies that have shown that engaging in agricultural activity can improve food security status in developing countries [ 29 , 69 , 70 , 71 , 72 ]. A study by Pawlak and Kolodziejczak (2020) found that increasing agricultural activities is a key driver of improving food availability and access in rural areas of developing countries [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…One of the reasons for this agricultural underperformance has been attributed to farm size. Herrera et al (2021) report that over half of respondents in northeastern Madagascar ascribed their experiences of food insecurity to the limited size of their agricultural plots. Small farm size has also been found to have a significant negative effect on food security in other contexts as well (e.g., Ethiopia, Bogale and Shimelis, 2009).…”
Section: Assets Dietary Diversity and Food Securitymentioning
confidence: 99%
“…Contrary to adopting a scattershot approach, others have found that, in Madagascar, focusing more intensively on a smaller number of crops led to better food insecurity outcomes, particularly when those crops were sold. For example, Herrera et al (2021) found that among smallholder farmers in northeastern Madagascar, half of their study population grew just two of the top crops (rice and vanilla) and that the probability of household food insecurity was lower when both of these crops had high yields. However, it is important to note that, as their study area is the leading region of vanilla production in Madagascar with a well-established international export market, these findings are not applicable to all parts of the country.…”
Section: Assets Dietary Diversity and Food Securitymentioning
confidence: 99%
“…Despite expanding agricultural land to support the country’s rapidly growing population, food production has fallen short of projections, and food insecurity still affects more than half of the population [ 64 , 65 ]. In Madagascar, food insecurity may result from the country’s agricultural sector’s low production, exacerbated by several factors, including climate change, insecure land tenure, and inadequate funding [ 66 ]. Due to these factors, the sector’s labor supply has decreased, leading to a fall in agricultural productivity.…”
Section: Discussionmentioning
confidence: 99%